2022
DOI: 10.1182/bloodadvances.2021005149
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning–based scoring models to predict hematopoietic stem cell mobilization in allogeneic donors

Abstract: Mobilized peripheral blood has become the primary source of hematopoietic stem cells for both autologous and allogeneic stem cell transplantation. Granulocyte Colony-Stimulating Factor (G-CSF) is currently the standard agent used in the allogeneic setting. Despite the high mobilization efficacy in most donors, G-CSF requires 4-5 days of daily administration, and a small percentage of the donors fail to mobilize an optimal number of stem cells necessary for a safe allogeneic stem cell transplant. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Based on our finding of powerful information that characterizes diseases, we tried to establish a machine learning model to distinguish chronic autoimmune diseases. Several reports have proven that the random forest (RF) machine learning method would give a high accuracy in disease classification when abundant features were included ( 71 , 72 ), and another reason for the random forest model was its interpretability—each gene contribution in the RF machine learning model was visible. Our area under curve (AUC) score for SLE indicates that our machine learning model has the potential to become an efficient tool for accurate diagnosis of SLE at the single-cell RNA level.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our finding of powerful information that characterizes diseases, we tried to establish a machine learning model to distinguish chronic autoimmune diseases. Several reports have proven that the random forest (RF) machine learning method would give a high accuracy in disease classification when abundant features were included ( 71 , 72 ), and another reason for the random forest model was its interpretability—each gene contribution in the RF machine learning model was visible. Our area under curve (AUC) score for SLE indicates that our machine learning model has the potential to become an efficient tool for accurate diagnosis of SLE at the single-cell RNA level.…”
Section: Discussionmentioning
confidence: 99%
“…A large retrospective study of donors mobilized with standard G‐CSF (n = 1025) and various other mobilization strategies available as Phase I/II trials (GM‐CSF, n = 40; G‐CSF + GM‐CSF, n = 167; GM‐CSF + plerixafor; plerixafor, n = 88; and BL‐8040, n = 18) was conducted by Xiang et al 27 The authors found that among allogeneic donors, cytokine‐based mobilization strategies (G‐CSF or in combination with GM‐CSF) induce higher CD34 cell yield after 4‐5 consecutive days of treatment, while CXCR4 antagonists (plerixafor and BL‐8040) induce significantly less but more rapid, same‐day mobilization 27 …”
Section: G‐csf and Cxcr4 Antagonistsmentioning
confidence: 99%
“…15 MGTA-145 Single arm trial; Grade 1 pain (bone pain) most common, seen in 11/25 (44%) with 9/25 (38%) experiencing acute-onset bone pain with MGTA-145 (duration 7 min, range 3-28). 35 At last, follow up, 18/25 completed transplant with MGTA-145 mobilized graft with receipt of a median (range) of 3.5 (2.2-8.1) Â 10 6 CD34/kg and median (range) days to neutrophil engraftment 15 (11)(12)(13)(14)(15) and platelet engraftment 17.5 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). 35 mobilization.…”
Section: Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…Both supervised ML approaches have achieved 89% and 97% accuracies, respectively, for the hPSCs classification system. Recently, the ML approach has also been implemented to predict allogeneic stem cell donors from the granulocyte colony-stimulating factor (G-CSF) of HSC ( Xiang et al, 2022 ). The established prediction methods were performed by cross-validation (10-fold) with appropriate hyper-parameter using a grid search technique.…”
Section: Evolution Of Cell Analysis Approachesmentioning
confidence: 99%